2021
DOI: 10.47115/jshs.995746
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Personality Traits and Lifelong Learning Tendencies of Midwifery Students

Abstract: Amaç: Bu araştırma ebelik öğrencilerinin kişilik özellikleri ve yaşam boyu öğrenme eğilimleri arasındaki ilişkinin belirlenmesi amacıyla yapılmıştır.Yöntem: Analitik-kesitsel tipte olan bu araştırma Türkiye'nin doğusunda bulunan bir üniversitenin Sağlık Bilimleri Fakültesi Ebelik Bölümü öğrencileri ile yürütülmüştür. Araştırmanın örneklemini 187 ebelik öğrencisi oluşturmuştur. Çalışmanın verileri "Kişisel Bilgi Formu", "Beş Faktör Kişilik Özellikleri Ölçeği (BF-KÖÖ)" ve "Yaşam Boyu Öğrenme Eğilimleri Ölçeği (Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Mammadov (2021) aimed at the relationship between five-factor model of personality and academic performance and found out that personality traits played a significant role in predicting academic performance. Benli et al (2021) focused on the relationship between nursing students' personality traits and lifelong learning tendency and demonstrated that extraversion, agreeableness and conscientiousness affected lifelong learning positively and emotional instability negatively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mammadov (2021) aimed at the relationship between five-factor model of personality and academic performance and found out that personality traits played a significant role in predicting academic performance. Benli et al (2021) focused on the relationship between nursing students' personality traits and lifelong learning tendency and demonstrated that extraversion, agreeableness and conscientiousness affected lifelong learning positively and emotional instability negatively.…”
Section: Literature Reviewmentioning
confidence: 99%